Strategies for Improving Teacher Information Literacy as an Effort to Develop Professionalism in the Digital Era - Anisa Isti Yuslimah; Achmad Kurniady, Dedy; Nurdin (LPPM Universitas 17 Agustus 1945 Semarang, 2025)
In the digital era, teachers must not only master technology but also develop strong strong information literacy to support thoughtful, responsible, and contextually relevant pedagogical practices. This study aims to identify comprehensive strategies to enhance teachers’ information literacy as part of their professional development. Using a Systematic Literature Review (SLR), ten empirical studies published within the past five years were selected from Scopus, Web of Science, and Google Scholar, employing the PRISMA protocol and Boolean search techniques. Thematic analysis revealed five key strategies: integrating digital media into teaching, providing professional development programs, fostering collaborative learning communities, promoting innovative and reflective information use, and strengthening policy support. These strategies collectively foster teachers’ ability to think reflectively, act responsibly in information use, and apply contextually grounded pedagogical approaches in their classrooms. The study concludes that improving teachers’ information literacy requires a multidimensional approach that combines pedagogical innovation, continuous digital training, and institutional backing. The proposed framework offers practical insights for schools, policymakers, and teacher educators in designing adaptive, sustainable, and context-sensitive models for teacher professional growth in the digital age.